Harnessing the impact of beneficial microorganisms to control Meloidogyne incognita in tomato cultivation across diverse environments - Win Lai Lai Swe; Ferenc Tóth; Renáta Petrikovszki; Márta Ladányi; József Fail (Egyptian Journal of Biological Pest Control)
Abstract Background Tomato (Solanum lycopersicum L.) can overcome productivity challenges caused by plant-parasitic nematodes, especially Meloidogyne incognita. M. incognita is the most harmful polyphagous endoparasitic nematode of various cultivated crops globally and causes huge yield losses. The use of traditional chemical nematicides poses environmental and health risks, which is why safe alternatives are being explored. This study aimed to find alternatives to peat as a potting medium and evaluate their effectiveness in enhancing plant resilience against nematodes. Specifically, the study assessed the efficacy of four biocontrol agents (Trichoderma asperellum, Beauveria bassiana, Fusarium proliferatum and Bacillus mojavensis) in peat-based and compost-based potting media under open-field and greenhouse conditions. Result The research analyzes their impact on plant growth performance and their capacity to mitigate the severity of galling, the primary symptom caused by M. incognita in tomato cultivation. The results showed insignificant difference between peat and compost-based media in open-field (F(1,101) = 0.001, p = 0.97) and greenhouse (F(1,90) = 2.53, p = 0.12) experiments. However, biocontrol agents differed significantly in effectiveness (open field: F(4,101) = 5.85, p < 0.001; greenhouse: F(4,90) = 15.88, p < 0.001). B. mojavensis reduced the gall index by 81.24% in compost-based medium, and B. bassiana reduced it by 68.86% in peat-based medium. Conclusion This study unequivocally demonstrated the remarkable efficacy of F. proliferatum and T. asperellum in promoting aboveground plant development. The application of biocontrol agents F. proliferatum, T. asperellum, B. bassiana and B. mojavensis resulted in a substantial 25–81% reduction in nematode galling index compared to the untreated control.